Filsafat Pendidikan Islam Dalam Menyikapi Pengetahuan Kontemporer Tinjauan Keseimbangan Ilmu Pengetahuan dan Keimanan - Muhammad Zulkhaidir; Yoga Febrian; Herlini Puspika Sari (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The background of this research is to analyze how Islamic Education Philosophy can act as a conceptual framework in addressing contemporary knowledge, especially in creating a balance between science and faith. In the modern era, the development of science and technology is increasingly advanced and developing more rapidly, so that new challenges arise in aligning knowledge with religious values ​​and faith. This research contributes to the understanding of how Islamic Educational Philosophy can be a relevant guide in overcoming the complex challenges faced by educational institutions in integrating contemporary knowledge with Islamic values. The implications of this journal can be used as a basis for developing better educational strategies that meet the demands of the times. Keywords: Philosophy of Education. Keywords: Philosophy of Islamic Education, Contemporary Knowledge, Faith